Evaluation of Social Capital Based on Organizational Resilience in Financial Startup Ecosystems - Amiri, Reza; Divsalar , Hedieh (Digital Transformation and Administration Innovation, 2025)
This study investigates the evaluation of social capital based on organizational resilience in financial startup ecosystems. In this research, using the thematic analysis method, 21 indicators related to assessing the efficiency of social capital were identified. To screen and ensure the significance of these indicators and to select the final indicators, the fuzzy Delphi method was applied. In this process, experts’ opinions were collected and analyzed using triangular fuzzy numbers and a 7-level fuzzy scale. The results showed that social capital and organizational resilience in startups play a vital role in strengthening their ability to cope with crises and rapid environmental changes. Social relations and communication networks enable startups to access informational, financial, and advisory resources during crises and to utilize them for innovation and growth. The present research also highlights the importance of strengthening communication networks and effectively exploiting social resources in times of crisis, introducing these approaches as strategies for enhancing resilience and the success of startups within financial ecosystems.